2021
DOI: 10.1186/s12871-021-01396-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound predicts clinical course but not outcome in COVID-19 ICU patients: a retrospective single-center analysis

Abstract: Background Point-of-care lung ultrasound (LU) is an established tool in the first assessment of patients with coronavirus disease (COVID-19). Purpose of this study was to evaluate the value of lung ultrasound in COVID-19 intensive care unit (ICU) patients in predicting clinical course and outcome. Methods We analyzed lung ultrasound score (LUS) of all COVID-19 patients admitted from March 2020 to December 2020 to the Internal Intensive Care Unit, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…During the in-hospital transfer, there can be some factors, such as unpredictable changes in illness, lack of monitoring and treatment equipment, lack or exhaustion of medical staff, and other factors, leading to malignant events during the transfer of patients in the hospital [ 22 ]. Some academics believe that pulse oximetry, blood pressure fluctuations, hypoxia, and hypotension are used as indicators to assess safe transport.…”
Section: Discussionmentioning
confidence: 99%
“…During the in-hospital transfer, there can be some factors, such as unpredictable changes in illness, lack of monitoring and treatment equipment, lack or exhaustion of medical staff, and other factors, leading to malignant events during the transfer of patients in the hospital [ 22 ]. Some academics believe that pulse oximetry, blood pressure fluctuations, hypoxia, and hypotension are used as indicators to assess safe transport.…”
Section: Discussionmentioning
confidence: 99%
“…AH-Plus paste has good spatial stability and fluidity and can conform to the shape of the root canal after forming. The formaldehyde content of the paste is high, which can effectively control the inflammation of the infected root canal [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of LUS in COVID-19 patients is still controversial. Persona et al suggested that the LUS score is not as reliable as in the non-COVID-19 patients [ 8 ], whereas Stecher et al stated that the LUS in ICU COVID-19 patients predicts the clinical course but not the outcome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%